2018
DOI: 10.14744/nci.2018.89411
|View full text |Cite
|
Sign up to set email alerts
|

The effects of barnidipine on an experimental ischemia reperfusion model of spinal cord injury and comparison with methyl prednisolone

Abstract: OBJECTIVE: Increased intracellular calcium concentration plays an important role in the secondary mechanism of spinal cord injury. In the presenting experimental study, we aimed to evaluate the healing effect of barnidipine, which has a high affinity for L-type calcium channels, on acute spinal cord injury and to compare its effects with those of methylprednisolone. METHODS: A total of 32 Spraque Dawley albino adult female rats were divided into 4 groups; group 1: sham-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the use of drugs, such as steroidal anti-inflammatory, that block the acute inflammatory response leads to more neurological damage in the SCI model than when this blockade does not occur [18,20,35] . One of the hypotheses for this worsening is intrinsically associated with the complexity of the phenotypic polarization that microglia and macrophages can acquire [18,21,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the use of drugs, such as steroidal anti-inflammatory, that block the acute inflammatory response leads to more neurological damage in the SCI model than when this blockade does not occur [18,20,35] . One of the hypotheses for this worsening is intrinsically associated with the complexity of the phenotypic polarization that microglia and macrophages can acquire [18,21,25] .…”
Section: Discussionmentioning
confidence: 99%